Les ressources en eau à Mostaganem, état actuel et contraintes de distribution - RAKEB, Lalia (My University, 2020)
The aim of this study is to highlight the state of conventional and non-conventional water resources in the wilaya of Mostaganem. Conventional resources which include surface and underground water are no longer sufficient to meet the needs of growing urban, agricultural and industrial consumption. Therefore, the recourse to non-conventional resources through sea water desalination and wastewater purification techniques have made it possible to make up the water deficit not only in drinking water supply (AEP) but also in crop irrigation. The Directorate of Water Resources (DRE) and the Algerian's Water (ADE) are the two structures that manage the water sector in Mostaganem and are faced with various operating and equipment constraints that need to be circumscribed.
Keywords: conventional and non-conventional water resources; wilaya of Mostaganem; mobilization and distribution constraints